THE MORPHOLOGICAL TYPOLOGY ANALYSIS OF SUNDANESE INFIX AS PLURAL MARKER - Hendar, (International Journal of Psychosocial Rehabilitation, 2020)
This research is focused on Sundanese language spoken by more than 30 million of Sundanese people, an Austronesia ethnic group in West Java and Banten province which is located at the western part of the Indonesian island. This ethnic group deals mainly with the morphological typology of Sundanese infixes. The objectives of this research, however, are 1) to find out the kinds of Sundanese infixes showing plural markers, 2) word syntactic categories using Sundanese infixes that show plural forms, and 3) the meaning of the words analyzed. The main data sources of this qualitative research are taken from both books and written information that already existed about the language studied and sources originating from native speakers of the language studied (Mallinson and Blake,1981). The results of the research show that 1) there three kinds of Sundanese infixes -ar-, -um-, and -in-, while -al- is the allomorph form of infix -ar-, and the only Sundanese infix showing plural marker is -ar-, 2) the syntactic categories of the words using Sundanese infix are Noun (N) as in budak (child) barudak (children), Verb (V) as in bobo (sleep)  barobo, Adjective (Adj.) as in geulis (beautiful)  gareulis and Adverb (Adv.) as in di jero (inside)  di jarero, 3) The grammatical category of -ar- infix refers to number showing plural marker, and the grammatical meanings of -ar- occurred to Noun (N), Verb (V), Adjective (Adj.) and Adverb (Adv.) are respectively plural (Noun), many persons who (Verb), many person who are (Adj.) and many persons who are (Adv.)